Association of Lower COMT Activity Alleles with Aggressive Traits in Male Youth with Conduct Disorder Living in a Correctional Facility - Lucija Tudor; Josip Podobnik; Gordana Nedic Erjavec; Matea Nikolac Perkovic; Jaanus Harro; Margus Kanarik; Darko Marcinko; Dubravka Svob Strac; Melita Cusek; Vlatka Kovac; Nela Pivac (Biomolecules)
Aggression constitutes a significant behavioral issue associated with delinquent behavior, commonly observed in youth diagnosed with conduct disorder (CD) and living in correctional facilities. Catechol-o-methyl-transferase (COMT) gene variants modify the environmental sensitivity associated with the risk of aggression. This study evaluated the association of COMT rs4680 and rs4818 polymorphisms with aggressive behavior in 341 male adolescents living inside and outside a correctional facility, with or without a diagnosis of CD. Aggression was assessed using the Hare Psychopathy Checklist: Youth Version (PCL-YV), Modified Overt Aggression Scale (MOAS) and Swanson, Nolan and Pelham Questionnaire. COMT rs4680 and rs4818 polymorphisms were genotyped using TaqMan SNP Genotyping Assays. A similar prevalence of the COMT genotypes or haplotypes was found between adolescents with or without CD, suicidal behavior, or detention in correctional facility. In youth with CD, the COMT rs4680 A allele was associated with higher MOAS verbal aggression, aggression toward objects, irritability (subjective and open), and PCL-YV interpersonal domain scores compared with carriers of the COMT rs4680 G allele. COMT rs4818 GC carriers with CD had higher scores on the MOAS subjective irritability than GG heterozygotes. These novel findings revealed the association of lower COMT rs4680 and rs4818 activity alleles with aggression in detained male adolescents with CD.